Simulation of Vulnerability to Geological Disaster in Coal Mine Based on System Dynamics. (16th June 2022) - Li, Lei; Zhi, Mei; Li, Ruihan; Wang, Siwei; Cao, Lirong
Abstract : The irrational mining of coal mines can cause damage to the geological environment, resulting in the frequent occurrence of geological disasters and high risk. In order to deeply explore the influence mechanism of coal mine geological disaster vulnerability, the three characteristic indicators of exposure, sensitivity, and adaptability proposed by the VSD vulnerability framework were taken as the starting point, and the indicator weights were determined by using the order graph method. The system dynamic model of coal mine geological disaster vulnerability was established and simulated. The results show that the exposure and sensitivity decrease gradually, and adaptability shows a gradual upward trend within one simulation period. When the parameter values of each subsystem were increased by 50%, the management subsystem was the key subsystem that affected the exposure and adaptability, and the exposure and adaptability variation decreased by 11.704% and 17.900%, respectively. The key subsystem affecting sensitivity was the equipment subsystem, and the sensitivity variation decreased by 18.958%.In order to reduce the vulnerability risk of geological disaster in coal mines and improve the safety management of the project.